Caresharing - Eleanor Krassen Covan (Grounded Theory Review: An International Journal)
This paper presents research findings generated from a study of the structure of a caresharing system for the elderly who reside in a Florida retirement community during the last decade of the twentieth century. A caresharing system is a combination of strategies employed in order to maximize pleasure and minimize losses that might otherwise be associated with communal and individual aging processes. In this instance, the caresharing system entailed a series of conscious efforts to hide frailty in the community. Consequences of such caresharing systems and implications for future retirement communities are discussed.